Kader hidup sehat dalam upaya promotif penyakit denegeratif - Emy Huriyati; Prima Dhewi Ratrikaningtyas; Siti Rahmah Projosasmito; Arta Farmawati (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2019)
Degenerative diseases occur because of interactions between genetics and lifestyle. The prevalence of non-communicable diseases in Sleman Regency is higher than the provincial average and occupies the second position in Daerah Istimewa Yogyakarta (DIY) or Special Region of Yogyakarta. The prevalence of diabetes mellitus 3.1% and central obesity is 29.8%. Health cadres have routinely carried out posyandu activities but have a role in preventing the risk of degenerative diseases which have not gone well. Research methods conducted with quasi-experimental one group pre-test and post-test designs on health cadres who were given counseling, tutorial, and discussions. The post test material was the cadre's knowledge before counseling and discussion were held. The measurement results are analyzed using quantitatif and pair t test analysis. The results of material delivery did not have a significant effect on the increase in knowledge of degenerative diseases p = 0.225 known from the pre-test (4.3 ± 1.6) and post-test (4.8 ± 1.4) with an increase in the mean of 0.4. Although statistically does not show significance, there is an increase in the value between pre and post test. There is an increase in the average knowledge before and after counseling.